A CLASSROOM ACTION RESEARCH; INCREASING STUDENTS’ ENGLISH VOCABULARIES USING WORD-SEARCH PUZZLE GAME - Aneke Kusherawati; Musytasyfa Thabib Kariadi; Novita Pri Andini (LEAD (Language, Education and Development), 2023)
This research aims to find out the implementation of Word Search Puzzle game as a learning method in teaching English vocabulary. This research also aims to find out whether Word Search Puzzle game increase students’ English vocabulary or not. The population and sample is at grade XI Science 6 at MAN 2 Banyumas in the academic year of 2023/2024. This research used Classroom Action Research (CAR) design in two cycles. The data collection method used mixed method; qualitative data and quantitative data collection method. The result of this research showed that; (1) The implementation of Word Search Puzzle game as a learning method at grade XI Science 6 of MAN 2 Banyumas was successful. (2) The result of pre-test showed that the average score was 57.7, while in post-test 1 the average score increased to 79.1. It means that the increase in average score from pre-test to post-test 1 was 21.4. Then in post-test 2 the average of students’ scores increased again to 86.3. It means that the increase in average score from post-test 1 to post-test 2 was 7.2. Based on the research findings of this research, it is concluded that the implementation of Word Search Puzzle game was successfully in increasing students’ English vocabularies at grade of XI Science 6 of MAN 2 Banyumas. Students also got an increase in theirs scores after the researcher implemented Word Search Puzzle game as a learning method.